Teatralny Lane: the History of the Buildings, Architecture and Owners of the Houses of the Central Part of Kharkiv at the Beginning of 20th Century - Нестеренко, Вікторія (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
The article is devoted to the development of Kharkiv urban space at the begining of XX century on the example of Teatralniy lane. It was situated in the central part of the city. On the base of “Value papers” and reference books the conclusions of building, infrastructure and population on the lane were made. The conclusions were connected with general development of the city.